Analysis of Reading Behavior and Influencing Factors of Preschool Children in Rural China - Zhu, Yunfei (International Journal of Social Sciences and Public Administration, 2024)
The purpose of this paper is to analyze the reading behavior of preschool children in rural China and its influence by their family and socio-cultural environment. The study builds a theoretical framework based on theories of reading behavior research, and empirically analyzes the influencing factors using appropriate research design and data collection methods. The findings reveal that family background, such as parents' education level and family economic situation, has a significant influence on children's reading behavior; meanwhile, the social and cultural environment and kindergarten reading education also play an important role in promoting preschool children's interest in reading and the formation of reading habits. The conclusion provides empirical support for how to improve the reading behavior of rural preschool children, and is of reference value for the formulation and implementation of related policies.